1982
DOI: 10.2307/3898535
|View full text |Cite
|
Sign up to set email alerts
|

Nitro Compounds in Introduced Astragalus Species

Abstract: Leaves of foreign Astragdus species were examined for the presence and type of poisonous aliphatic nitro compounds. Twenty-two (24%) of the 92 species examined tested positive for nitro compounds and 70 (76%) tested negative. Three nitrobearing species, Astragalus bodeanus Fisch., Astragahs isfalranicus Boiss., and Astragalus siliquosus Boiss. synthesized 3-nitro-l-propanol (3NPOH). The other nitro-bearing species synthesized 34tropropionic acid (INPA). Ten taxonomic sections had a high percentage of nitro-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A large number of New and Old World species of Astragalus (Leguminosae) contain glycosides of 3-nitropropanol (NPOH; Williams, 1982;Williams and Davis, 1982). Timber milkvetch (A. miser var.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of New and Old World species of Astragalus (Leguminosae) contain glycosides of 3-nitropropanol (NPOH; Williams, 1982;Williams and Davis, 1982). Timber milkvetch (A. miser var.…”
Section: Introductionmentioning
confidence: 99%
“…The other species are distributed from Spain to China. Eight of these species have been examined and all synthesize nitro compounds, Analysis of fresh material of four species revealed that the plants synthesized high concentrations of nitro compounds (28 to 84 mg N0 2 /g of oven dry plant) that hydrolyzed to 3 -NPA (16,18). On the basis of these data, one could predict that the other two species, A. discessiflorus Gontsch.…”
Section: Resultsmentioning
confidence: 99%
“…Other taxonomic sections in which one or more species synthesize 3-NPA are Astragalus, Buceras, Glycyphyllos, Hemiphaca, Hypoglottis, Oxyglottis, Proselius, and Talievia (16).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a plethora of works regarding other species of the same genus exists. The Astragalus species were employed as forage for animals, albeit many species were found to be toxic, and responsible for causing locoism in cattle [3,4]. In both folk and modern medicine, several Astragalus spp.…”
Section: Introductionmentioning
confidence: 99%